2010
DOI: 10.1016/j.psychres.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards long-acting depot antipsychotics: A survey of patients, relatives and psychiatrists

Abstract: In many countries fewer than 20% of individuals with schizophrenia receive depot antipsychotic medication. Frequently stated reasons are psychiatrist's, patient's and relative's objections to depot treatment. This is the first study that directly compares the attitudes to depot antipsychotics of psychiatrists, patients and relatives. A semi-structured questionnaire about their attitudes to depot antipsychotics was completed by 255 participants (83 patients diagnosed with schizophrenic disorder, 81 psychiatrist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
135
5
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(159 citation statements)
references
References 24 publications
(31 reference statements)
11
135
5
8
Order By: Relevance
“…For example, in a survey of perceptions about medication use, patients with schizophrenia were less likely to agree that the good things about medication outweigh the bad (61% of patients) than were psychiatrists (81%) or family members (80%). 130 Stakeholder groups may also differ in their attitudes toward other issues, such as medication cost, access to care, and reimbursement.…”
Section: Best Practices To Maximize Lai Acceptability and Experience mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a survey of perceptions about medication use, patients with schizophrenia were less likely to agree that the good things about medication outweigh the bad (61% of patients) than were psychiatrists (81%) or family members (80%). 130 Stakeholder groups may also differ in their attitudes toward other issues, such as medication cost, access to care, and reimbursement.…”
Section: Best Practices To Maximize Lai Acceptability and Experience mentioning
confidence: 99%
“…128,129 In many cases, physician beliefs and perceptions about LAIs may prevent patients from learning that LAIs are a potential option. 130,131 For example, in a study of communication patterns in the offer of LAIs made by psychiatrists to patients with schizophrenia at 10 health clinics, psychiatrists generally presented LAIs in a negative light, resulting in only 11 of 33 LAI recommendations (33%) being accepted by patients. 132 However, during a postvisit interview, during which LAIs were presented in a more positive light and with more information, 27 of the 28 patients (96%) who declined the initial recommendation changed their mind, stating that they actually would be willing to try LAI treatment.…”
mentioning
confidence: 99%
“…The second example comes from Switzerland, the country with the arguably lowest rates of LAI use in Europe (5%). Among three study groups (patients, psychiatrists, and relatives), the most favorable view of depot formulation was held by the relatives (44). Patients without LAI experience reported that their psychiatrists did not recommend change to depot (91%) and even failed to inform them about this option (79%).…”
Section: Patients' Perception Of Lai Antipsychoticsmentioning
confidence: 99%
“…16,17 However, reports like that of Kane et al 1 remind us that LAIs could be well used as an option in the early phase of an episode with both good tolerability and efficacy depending, of course, on the individual patient and the antipsychotic compound.…”
mentioning
confidence: 99%